Investigating Vocabulary Acquisition among Young Learners through Contemporary and Traditional Games in Interactive EFL Settings - Hidayatullah, Ahmad Syauqi; Sudirman, Anselmus; Ardhian, Trio; Vijayanti, Ditha; Sari, Sinta Ratna; Sari, Apri Lina Laksita (Dedikasi Sains dan Teknologi (DST), 2025)
This article examines vocabulary acquisition among young EFL learners. Various ways for vocabulary instruction have faced challenges concerning interest and retention, leading instructors to explore interactive learning methods to enhance vocabulary acquisition significantly. The instructional activities utilized games, songs, films, and narratives to augment intrinsic motivation and contextualize language application that can enhance vocabulary retention and conversational abilities. The study comprises three weekly educational sessions that utilize diverse multimedia materials to maintain learner interest and improve learning outcomes. Results indicate significant progress in vocabulary acquisition, demonstrating the successful utilization of interactive learning tools. These findings offer significant insights into practical implications for enhancing EFL teaching among young learners and lay the groundwork for future study on long-term vocabulary retention. This study provides insights for instructors seeking to adopt more engaging pedagogical practices and improve language learning experiences for young learners.